La construction de la frontière de facto abkhazo-géorgienne, entre enjeux sécuritaires, politiques et identitaires - Ariane Bachelet; Yann Richard (L'Espace Politique)
This article examines how is constructed the border of a de facto State, taking the disputed border between Abkhazia and the territory administered by Georgia as a case-study. It is based on field research covering the period 2015-2018, with several visits to Abkhazia, ten border crossings and a series of formal interviews and informal exchanges. Attention is focused on the individual actors, political actors and institutions that build the border area physically and symbolically. The Abkhaz authorities are pursuing a policy of territorial re-appropriation in cooperation with Russia (delimitation and security of the border, flow control and redevelopment of the identity space). For their part, the Tbilisi authorities are implementing a policy of reconciliation and attractiveness by promoting the development of the border area. In addition, they are trying to make this border invisible because they are challenging its status as an international boundary. Indeed, the conflict analysed in this article does not concern the line between Abkhazia and the rest of Georgia. It is about his status. Is it an inter-state border in the traditional sense of a boundary between two sovereign States? Or an administrative limit within the Georgian State? The evolution of this disputed boundary towards de jure international border status stricto sensu or towards administrative boundary status depends on the decisions taken by the two riparian political entities (Georgia and Abkhazia). However, on the ground, time seems to be a factor in stabilizing the de facto situation and the possible consolidation of this border is a possible hypothesis.